Reaksi Pasar Atas Momentum Hari Raya Idul Fitri Tahun 2019 - Nanda, Gede Rama Wirya; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2020)
This study aims to determine the market reaction to the momentum of Idul Fitri in 2019. This research is an event study with an observation period of 14 days. The study was conducted at companies classified as the Jakarta Islamic Index (JII) in 2019. The population in this study was 30 companies. The sampling method used is the saturated sample method. Samples obtained were 30 companies. Market reaction to the momentum of Idul Fitri in 2019 is measured using abnormal returns and trading volume activity. The data analysis technique used is the one-sample t-test. The test results show that there is a market reaction during the Idul Fitri in 2019 which is indicated by a significant abnormal return and trading volume activity around the event date. This shows that Idul Fitri in 2019 caused a market reaction because of there was an information content of the event. Keywords: Event Study; Abnormal Return; Trading Volume Activity.